Free Drawing Group Activity Therapy: A Strategy to Reduce Loneliness in Elderly Nursing Home Residents - Heni Nurhaeni; Mawar Meilita; Widagdo, Wahyu (Universitas Airlangga, 2025)
Introduction: Elderly individuals are particularly vulnerable to psychosocial issues, one of the most common being loneliness. If left unaddressed, loneliness can lead to a reduced quality of life and an increased risk of mental health disorders, including depression and even suicidal behavior. One effective non-pharmacological intervention to reduce loneliness is group activity therapy, such as free drawing. This study aimed to identify the characteristics of the elderly, assess the level of loneliness they experience, and analyze the effect of free drawing activity therapy on reducing loneliness among elderly residents in the Nursing Home. Method: A quasi-experimental design was employed, utilizing a two-group pretest-posttest approach. A total of 60 elderly participants were selected through purposive sampling and divided evenly into intervention and control groups. The intervention group received free drawing activity therapy sessions from March to April 2025 at PSTW Budi Mulia 3. Results: Data were analyzed using paired t-tests and independent t-tests. The findings showed a significant reduction in the mean loneliness score in the intervention group, from 48.57 to 41.87 (p = 0.001), while the control group experienced a slight increase from 50.40 to 50.70 (p = 0.445). Furthermore, there was a statistically significant difference in post-intervention loneliness scores between the two groups (p = 0.001). Conclusions: In conclusion, free drawing activity therapy significantly reduced loneliness among elderly residents in nursing homes and may serve as a practical non-pharmacological strategy to enhance their psychosocial well-being.